Functional Profiling of Antibody Immune Repertoires in Convalescent Zika Virus Disease Patients - Fahad, Ahmed S.; Timm, Morgan R.; Madan, Bharat; Burgomaster, Katherine E.; Dowd, Kimberly A.; Normandin, Erica; Gutiérrez-González, Matías F.; Pennington, Joseph M.; De Souza, Matheus Oliveira; Henry, Amy R.; Laboune, Farida; Wang, Lingshu; et al. (Frontiers in Immunology, 2021)
The re-emergence of Zika virus (ZIKV) caused widespread infections that were linked to Guillain-Barré syndrome in adults and congenital malformation in fetuses, and epidemiological data suggest that ZIKV infection can induce protective antibody responses. A more detailed understanding of anti-ZIKV antibody responses may lead to enhanced antibody discovery and improved vaccine designs against ZIKV and related flaviviruses. Here, we applied recently-invented library-scale antibody screening technologies to determine comprehensive functional molecular and genetic profiles of naturally elicited human anti-ZIKV antibodies in three convalescent individuals. We leveraged natively paired antibody yeast display and NGS to predict antibody cross-reactivities and coarse-grain antibody affinities, to perform in-depth immune profiling of IgM, IgG, and IgA antibody repertoires in peripheral blood, and to reveal virus maturation state-dependent antibody interactions. Repertoire-scale comparison of ZIKV VLP-specific and non-specific antibodies in the same individuals also showed that mean antibody somatic hypermutation levels were substantially influenced by donor-intrinsic characteristics. These data provide insights into antiviral antibody responses to ZIKV disease and outline systems-level strategies to track human antibody immune responses to emergent viral infections.